Application of Immobilized Proline on CNTs and Proline Ionic Liquid as Novel Organocatalysts in the Synthesis of 2‐Amino‐4H‐pyran Derivatives: A Comparative Study between Their Catalytic Activities. Issue 28 (5th October 2017) - Hajipour, Abdol R.; Khorsandi, Zahra
Abstract: The [BMIm][Pro] and Pro/MWCNTs (proline which supported on multi walled carbon nanotube) was synthesized and their activities in synthesis of various derivatives of 2‐amino‐4 H ‐pyrans in green media and room temperature conditions was investigated and compared. All the reactions resulted in moderate to excellent yields; however, reactions using Pro/MWCNTs catalyst were completed in relatively shorter reaction times. A novel heterogeneous Pro/MWCNTs was developed using immobilization of proline on MWCNTs via direct grafting amination approach for the first time. The reusability of two catalytic systems was also investigated. Abstract : A novel heterogeneous Pro/MWCNTs was developed using immobilization of proline on MWCNTs via direct grafting amination approach for the first time. And its application in the 2‐amino‐4 H ‐pyrans synthesis was compared with proline ionic liquid